2016
DOI: 10.1007/s11814-015-0244-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic method for measuring the gas holdup of gas-liquid bubbly flow in a small-diameter pipe

Abstract: Based on ultrasonic sound pressure attenuation, the ultrasonic pulse transmission method is proposed for measuring gas holdup in gas-liquid two-phase bubbly flows. Two ultrasonic transducers are positioned on opposite sides of a vertical upward pipe with an inner diameter of 20 mm. To obtain the relationship between ultrasonic attenuation and gas holdup, the mean value of the first pulse sequence of ultrasonic signals is first extracted as the measured signal. We used the quick closing valve method to obtain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Then SPL1(g) and SPL2(g) were calculated when the pipe is full of gas. A bubble with the diameter of 1 mm at (x,y) was put in the pipe full of water, the bubble in the oil-gas-water three-phase flow had several diameters, but the measurement of small bubbles is an important factor to limit the sensitivity of ultrasonic sensors [19]. Based on our previous research, the smallest bubble was 1 mm in diameter Two index termed average sensitivity S avg and homogeneous error SVP was introduced to give a quantitative optimization.…”
Section: Receiver1mentioning
confidence: 99%
See 1 more Smart Citation
“…Then SPL1(g) and SPL2(g) were calculated when the pipe is full of gas. A bubble with the diameter of 1 mm at (x,y) was put in the pipe full of water, the bubble in the oil-gas-water three-phase flow had several diameters, but the measurement of small bubbles is an important factor to limit the sensitivity of ultrasonic sensors [19]. Based on our previous research, the smallest bubble was 1 mm in diameter Two index termed average sensitivity S avg and homogeneous error SVP was introduced to give a quantitative optimization.…”
Section: Receiver1mentioning
confidence: 99%
“…Focusing on void fraction measurement in oil-gas-water three-phase flow, because of the heterogeneous distribution of the gas phase. The ultrasonic sensor consisted of single receiver is insufficient to accurately measure void fraction [19,20]. In this paper, a mutually perpendicular ultrasonic sensor (MPUS) system composed of two pairs of ultrasonic transducers positioned opposite to each other was designed to measure the void fraction of heterogeneous flow in oil-gas-water three-phase flow.…”
Section: Introductionmentioning
confidence: 99%
“…These measurement methods have their characteristics, and ultrasonic wave has unique advantages in medical and pipeline fluid parameter monitoring because it generally does not damage the measured flow field in the process of propagation and can achieve non-invasive and non-disturbing parameter detection [20,21]. Currently, widely used ultrasonic methods include the reflection method, transmission method, Doppler method, and imaging method [22]. In 2004, Vatanakful et al used a transmissive ultrasonic sensor to measure the dispersed phase holdup in a gas-liquid-solid three-phase flow [23].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al studied the effect of gas phase and solid phase on the response of an ultrasonic sensor in a gas-liquid-solid three-phase flow by measuring the velocity and attenuation of ultrasonic waves through the medium [24]. In 2016, Gong et al suggested an ultrasonic pulse transmission method based on the ultrasonic sound pressure attenuation theory for monitoring gas holdup in gas-liquid two-phase bubble flow [22]. In 2020, Jin et al used ultrasonic sensors and optical fiber sensors to investigate the measurement characteristics of gas holdup by ultrasonic sensors for typical flow patterns in oil-gas-water three-phase flows vertically rising with an inner diameter of 20 mm [25].…”
Section: Introductionmentioning
confidence: 99%